The Seal of the Prophet and his message lesson on Islamic Doctrine - Lari, Sayyid Mujtaba Musavi (The foundations of Islamic doctrine, 2008)
This book explains the Islamic view of Prophet hood and the particular role played by the Prophet of Islamic as the Seal of the Prophet. It also includes a summary account of the life of the Prophet of Islam